STUDI KASUS: DAMPAK KURIKULUM MERDEKA DAN DURASI MENGAJAR DILIHAT DARI MINAT PESERTA DIDIK SEKOLAH DASAR PADA PEMBELAJARAN MATEMATIKA - Nanda Putri Meilina; Fajar Setiawan; Kunti Dian Ayu Afiani (STKIP Subang, 2025)
This study aims to analyze the impact of the independent curriculum and teaching duration on elementary school students' interest in learning mathematics. This research is important to find out how the impact of the independent curriculum and teaching duration on student interest is carried out during learning, especially teachers facing a shorter teaching duration than the previous curriculum. The method used was qualitative with the research subjects being grade 4 students, grade 4 teachers and the principal of SD Muhammadiyah 2 Surabaya. Data collection techniques include observation, interviews, and documentation. The results of this study state that the independent curriculum and teaching duration seen from the interest of elementary school students in learning mathematics have a good impact on the implementation of learning, by using interactive media and utilizing students' talent interests which are positive values for schools. With an independent curriculum and flexible teaching duration students can explore their respective interests. This research is expected to provide insights for educators and policy makers of the Indonesian education curriculum in seeking the implementation of an independent curriculum.